ESSENTIAL OILS AND THEIR ANTIMICROBIAL EFFECTS - Sarimsakov Mahamadjalol Isakjonovich (Web of Journals Publishing, 2025)
This review explores the antimicrobial mechanisms, clinical applications, and therapeutic potential of essential oils, with a focus on pediatric and neonatal care. It highlights their ability to disrupt microbial membranes, inhibit metabolism, and suppress virulence factors. Evidence shows efficacy against multidrug-resistant pathogens, suggesting essential oils as valuable adjuvants amid rising antibiotic resistance. The review also addresses optimal formulations, delivery methods, and safety considerations, particularly for vulnerable populations. Future directions include nanotechnology-based delivery and standardized clinical protocols.
Keywords: essential oils, antimicrobial activity, antibiotic resistance, pediatric medicine, neonatal care, membrane disruption, volatile organic compounds, therapeutic applications, clinical microbiology, natural products